2017
DOI: 10.3892/ol.2017.6215
|View full text |Cite
|
Sign up to set email alerts
|

MLH1 expression predicts the response to preoperative therapy and is associated with PD-L1 expression in esophageal cancer

Abstract: Abstract. Programmed death-ligand 1 (PD-1/PD-L1) inhibition therapy demonstrates potential as a future treatment for esophageal cancer. Mismatch repair status and tumor PD-L1 expression are the candidate predictive biomarkers for response to this therapy. In colorectal cancer, mismatch repair-deficient tumors are associated with improved survival, although they are not sensitive to 5-fluorouracil-based chemotherapy. The purpose of the present study was to investigate the association between MutL homolog 1 (MLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
1
20
2
Order By: Relevance
“…This result was similar to those of previous studies, which demonstrated that approximately 85% of MLH1-negative gastric cancers were MSI-H [10,19]. In addition, since immunohistochemistry of MLH1 was shown in a previous report to be a reliable method to detect MMRD and MSI-H [20], MLH1 status evaluated by immunohistochemistry might be a useful alternative to MSI status as a biomarker in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to those of previous studies, which demonstrated that approximately 85% of MLH1-negative gastric cancers were MSI-H [10,19]. In addition, since immunohistochemistry of MLH1 was shown in a previous report to be a reliable method to detect MMRD and MSI-H [20], MLH1 status evaluated by immunohistochemistry might be a useful alternative to MSI status as a biomarker in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Findings about the associations between PD-L1 expression and prognosis of ESCC patients in the previous reports were controversial 19 , 22 , 28 , 29 , 32 - 38 . The majority of investigations reported that PD-L1 expression was associated with unfavorable prognosis of ESCC patients 19 , 29 , 32 - 35 , 37 , 38 . However, a few studies reported the opposite results 22 , 28 , 36 .…”
Section: Discussionmentioning
confidence: 89%
“…According to the search strategy in our study, we found 3 studies investigated the prognostic value of PD-L1 expression detected by IHC in tumor-infiltrating immune cells of EC. [ 12 , 18 , 20 ] In the study of Zhang et al, [ 12 ] tissue specimens from 344 patients with ESCC were obtained for IHC analysis of PD-L1 expression on tumor-infiltrating immune cells. The results demonstrated that PD-L1 expression on tumor-infiltrating immune cells is an independent prognostic factor in patients with ESCC and patients with positive immune cell PD-L1 expression had improved survival.…”
Section: Discussionmentioning
confidence: 99%